2018
DOI: 10.3233/jad-180084
|View full text |Cite
|
Sign up to set email alerts
|

Music and Dementia: Individual Differences in Response to Personalized Playlists

Abstract: Personalized music playlists are increasingly being used in health-care contexts to address the psychological and behavioral symptoms in people with dementia. However, there is little understanding of how people with different mental health histories and symptoms respond differently to music. A factorial experiment was conducted to investigate the influence of depression, anxiety, apathy, and cognitive decline on affective response to music. Ninety-nine people with dementia listened to three music playlists ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 45 publications
4
60
0
5
Order By: Relevance
“…Studies have shown that non-personalized music might increase anxiety and depression in patients with dementia. 6,25 It was vital to organize active song sessions in groups with staff present all the time. Several strategies related to music therapy are described, and distinction is often made between a receptive approach (listening to music) and an active approach (i.e., participating).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that non-personalized music might increase anxiety and depression in patients with dementia. 6,25 It was vital to organize active song sessions in groups with staff present all the time. Several strategies related to music therapy are described, and distinction is often made between a receptive approach (listening to music) and an active approach (i.e., participating).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been found in other studies. 6,25 People with dementia are as varied as people without it, and they have their own backgrounds, histories, and preferences. Music is found to be closely associated with each person's identity, history, and earlier life events, which are often linked to a particular type of music.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations